Accountability of Peer to Peer Lending Organizers to Lenders from a Responsibility Theory Perspective - Indah Sari, Yuliana; Ratna Januarita; Rini Irianti Sundary (KRTHA BHAYANGKARA, 2025)
The presence of Peer To Peer Lending in Indonesia emerged in 2015 and became a solution for Borrowers with easy requirements without collateral. Although peer to peer lending provides convenience for borrowers (borrowers) on the other hand peer to peer lending has an impact or risk for lenders (borrowers) namely the non-return of loan funds that have been given (lenders) to borrowers through the Peer To Peer Lending organizer, the non-return of funds as agreed, is considered a default, so that the Organizer can be held for the incident. This research is a normative and descriptive analytical research using primary legal materials such as POJK Number: 77 / POJK.01 / 2016 concerning information technology-based money lending services, POJK Number 18 / POJK.07 / 2018 concerning Consumer Complaints Services in the Financial Services Sector, and POJK Number 31 / POJK.07 / 2020 concerning the Provision of Consumer and Community Services in the Financial Services Sector, and Hans Kelsen's theory of responsibility. The results of this study indicate that the Theory of Responsibility initiated by Hans Kelsen says that a person is legally responsible for a certain act or that he bears legal responsibility, the subject means that he is responsible for a sanction in terms of a separating act. Hans Kelsen stresses that there must be sanctions that can be applied, the implementation of Hans Kelsen's Theory of responsibility is not realized in this case, because civil sanctions in the form of compensation that should be given by the organizer to the lender are not given so that equality of action in law is not realized which should be the law can protect the injured and weak parties.